2016
DOI: 10.3390/ijerph13111082
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Fine Particulate Matter Exposure and Risk of Cardiovascular Mortality: Adjustment of the Meteorological Factors

Abstract: Few studies have explicitly explored the impacts of the extensive adjustment (with a lag period of more than one week) of temperature and humidity on the association between ambient fine particulate matter (PM2.5) and cardiovascular mortality. In a time stratified case-crossover study, we used a distributed lag nonlinear model to assess the impacts of extensive adjustments of temperature and humidity for longer lag periods (for 7, 14, 21, 28 and 40 days) on effects of PM2.5 on total cardiovascular mortality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Indeed, it is estimated that more than 50% of the health burden of air pollution is through CVD [6]. Epidemiologic studies have linked short- and long-term air pollution exposure to increased risk for subclinical CVD [714], major cardiovascular events [1527], and cardiovascular mortality [2845, 27, 46, 47]. The proposed mechanisms include through the promotion of CVD risk factors [4867], as well as through increased systemic inflammation and coagulation [9••].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is estimated that more than 50% of the health burden of air pollution is through CVD [6]. Epidemiologic studies have linked short- and long-term air pollution exposure to increased risk for subclinical CVD [714], major cardiovascular events [1527], and cardiovascular mortality [2845, 27, 46, 47]. The proposed mechanisms include through the promotion of CVD risk factors [4867], as well as through increased systemic inflammation and coagulation [9••].…”
Section: Introductionmentioning
confidence: 99%
“…The usual analytic approach to control for weather is to include weather variables, typically temperature and humidity, in regression models that evaluate the effect of air pollution on mortality. However, an inappropriate set of weather variables and the correlations among weather variables as well as between weather variables and air pollution [ 84 , 85 ] could bias the estimate of the effect of air pollution on mortality. One alternate approach for controlling the potential confounding by weather is to use the synoptic categorization of weather.…”
Section: Discussionmentioning
confidence: 99%
“…The PM2.5 level can be used to determine the degree of air pollution. After being inhaled into the lungs, PM2.5 can further go into the human blood circulation via diffusion and reach nearly every organ of the body, causing cardiovascular diseases [ 3 ], bronchitis [ 12 ], asthma [ 12 ], and hypertension [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…PM2.5 is regarded as one of the most important air pollutants in many cities of China [ 2 ]. As air pollution caused by PM2.5 is intensifying in recent years, there has been a rising incidence of cardiovascular [ 3 ] and respiratory diseases [ 4 ]. One study [ 5 ] has shown that PM2.5 enters the human lungs via respiration and adheres to the lung epithelium.…”
Section: Introductionmentioning
confidence: 99%